Design and Development of Android-Based Interactive Learning Media for Basic Subjects in Computer and Telecommunication Network Engineering - Fadilla; Efrizon; Mahesi Agni Zaus; Vera Irma Delianti (Universitas Negeri Padang, 2025)
The advancement of educational technology plays a pivotal role in improving student engagement and learning outcomes, especially in vocational education. This study aims to design and develop an Android-based interactive learning media application for the Basic Computer and Telecommunication Network Engineering course targeted at Grade X students of SMK Negeri 1 Sijunjung. The development process adopted the ADDIE model, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The application integrates multimedia elements such as text, images, instructional videos, and interactive quizzes, and was built using the Flutter framework to ensure compatibility across Android devices. Validation was conducted through expert reviews and user feedback. Material experts rated the application with an average feasibility score of 93.3%, while media experts provided a score of 91.3%. Additionally, student feedback revealed a high level of acceptance with an average satisfaction score of 88.52%. These results confirm the application's validity and effectiveness in enhancing student motivation and facilitating independent learning. This study highlights the potential of mobile-based interactive media as a complementary tool in vocational education and offers a foundation for future development integrating adaptive and collaborative learning features.